Emerging graphene derivatives as active 2D coordination platforms for single-atom catalysts - Hrubý, Vítězslav; Zaoralová, Dagmar; Medveď, Miroslav; Bakandritsos, Aristeidis; Zbořil, Radek; Otyepka, Michal (Nanoscale, 2022)
Single-atom catalysts (SACs) based on graphene derivatives are an emerging and growing class of materials functioning as two-dimensional (2D) metal-coordination scaffolds with intriguing properties. Recently, owing to the rich chemistry of fluorographene, new avenues have opened toward graphene derivatives with selective, spacer-free, and dense functionalization, acting as in-plane or out-of-plane metal coordination ligands. The particular structural features give rise to intriguing phenomena occurring between the coordinated metals and the graphene backbone. These include redox processes, charge transfer, emergence, and stabilization of rare or otherwise unstable metal valence states, as well as metal-support and metal-metal synergism. The vast potential of such systems has been demonstrated as enzyme mimics for cooperative mixed-valence SACs, ethanol fuel cells, and CO2 fixation; however, it is anticipated that their impact will further expand toward diverse fields, e.g., advanced organic transformations, electrochemical energy storage, and energy harvesting.